Analysis of Student’s Mathematical Problem Solving Ability on HOTS Questions at MTS Ar-Raudhatul Hasanah Medan - Mara Samin Lubis; Ahmad Nizar Rangkuti (Didaktika: Jurnal Kependidikan, 2024)
This research aims to analyze students' mathematical problem solving abilities in Higher Order Thinking Skills (HOTS) on lines and angles. The research method used was descriptive analytical with the research subjects being class VIII students at MTs Ar-Raudhatul Hasanah Medan. Data was collected through a mathematical problem solving test with a focus on the HOTS aspect, namely providing a series of HOTS questions specifically designed to explore students' skills in dealing with complex aspects of Lines and Angles. The research results show that students show various levels of proficiency in solving complex problems that require critical thinking and in-depth understanding of line and angle material and that most students still experience difficulty in answering questions that require the application of HOTS. The implication of this research is to improve the mathematics curriculum at MTs Ar-Raudhatul Hasanah Medan by including more HOTS elements. This may include improvements to curriculum structure, emphasis on HOTS concepts, and integration of teaching methods that support the development of high-level problem solving